Multimedia As a New Approach for Learning in Physical Education - Kioumourtzoglou, Iordanis; Zetou, Eleni; Antoniou, Panagiotis (Arab Journal of Nutrition and Exercise (AJNE), 2022)
Aim: To present the relevant research results that enhance the possibilities presented today with the use of multimedia applications. An attempt was made to explain its importance in the learning process in general and motor skills in particular. At the same time, we try to define the implementation process and the flags that need attention for the best possible results. Nowadays the use of digital technology has reached very high levels. Especially in the last two years with the COVID-19 pandemic, where distance learning was most used. Teachers have learned to use these digital tools to create attractive lessons for their students, who are already introduced to digital technology in their lives. The use of multimedia in education, as many research suggests, is a modern learning tool in the classroom, but recently they have been used in both physical education and sport. The effectiveness of multimedia use is based on the theory of visualization of information that helps the student store this information in their memory for subsequent recall, make the course more attractive/pleasant, so students are motivated to learn. In PA and sports it is used as a helpful tool, since the master of learning is practice. The means used to present multimedia in the classroom can be tablets, mobile phones, a laptop with a large screen view at the same time.